Prognostic Value of Fluoro-D-glucose Uptake of Primary Tumor and Metastatic Lesions in Advanced Nonsmall Cell Lung Cancer - Xuan Nguyen; Van Nguyen; Minh Tran; Simone Maurea; Marco Salvatore (World Journal of Nuclear Medicine)
To assess the prognostic value of maximum standardized uptake value (maxSUV) of the primary tumor (maxSUV pt ), maxSUV of whole-body tumors (maxSUV wb ) and sum of maximum standardized uptake value (sumaxSUV) measured by the sum of maxSUVs of the primary tumor, metastatic lymph nodes, and metastatic lesions per each organ on fluoro-D-glucose-positron emission tomography/computed tomography in advanced non-small cell lung cancer (NSCLC). Eighty-three patients (49 male, 34 female) with advanced NSCLC were enrolled. Seventeen patients had Stage IIIA, 21 Stage IIIB, and 45 Stage IV. maxSUV pt , maxSUV wb , sumaxSUV, age, gender, tumor-cell type, T stage, N stage, overall stage, primary tumor size, and specific treatment were analyzed for correlation with overall survival. Median follow-up duration was 13 months. Fifty patients were dead during a median follow-up time of 11 months and 33 patients were alive with a median time of 15 months. Univariate analysis revealed that overall survival was significantly correlated with sumaxSUV (≥35 vs. <35, P = 0.004), T stage (T4 vs. T1-T3, P = 0.025), overall stage (IV vs. III, P = 0.002), gender (male vs. female, P = 0.029) and specific treatment (no vs. yes, P = 0.011). maxSUV pt and maxSUV wb were not correlated with overall survival with P value of 0.139 and 0.168, respectively. Multivariate analysis identified sumaxSUV, T stage, gender, and specific treatment as independent prognostic indicators. Patients with a sumaxSUV of ≥35 were 1.921 times more likely to die than those with a sumaxSUV of < 35 (P = 0.047). Median survival time was 14 months for patients with sumaxSUV ≥ 35 compared with 20 months for those with sumaxSUV < 35. In patients with metastatic NSCLC, sumaxSUV with cut-off of 35 was much more significant for survival prognosis (P = 0.021). sumaxSUV is a new prognostic measure, independent of tumor stage, gender, and specific treatment in advanced NSCLC. sumaxSUV may be better than maxSUV pt and maxSUV wb in prediction of survival. A large prospective cohort study is necessary to validate these results.